Метод повышения согласованности индивидуальных экспертных ранжирований при их агрегации - Каденко, С.В.; Цыганок, В.В. (Проблемы управления и информатики, 2012)
Описано метод організації зворотного зв’язку з експертами при побудові групового ранжування альтернатив. Результатом роботи методу є множина індивідуальних експертних ранжувань множини альтернатив, які під час агрегації дозволяють отримати транзитивне групове відношення переваг на даній множині. A method of organizing feedback with experts while building a group ranking of alternatives is considered. The final result of the method’s work is a set of individual expert alternative ranking implying the possibility of obtaining a transitive group preference relation on given set after aggregation.